Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper presents the projections on the fiscal and external profiles for Norway, and discusses the long-term prospects and policy options. The study evaluates the details and implications of the system of social insurance schemes; and long-term profile of oil-related exports and income. The paper highlights the economics behind long-term projections for the non-oil current account. The study focuses on the implications of centralized bargaining for the labor market, and explores its continued viability.